PENGARUH INTENSITAS MENONTON TAYANGAN SINETRON DARI JENDELA SMP TERHADAP PERUBAHAN PERILAKU REMAJA DI SMP NEGERI 4 SEMENDE DARAT LAUT - Riki Suhendra; Nurseri Hasnah Nasution; Muslimin Muslimin (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2021)
Adolescence is a period of transition that is very sensitive to changes in behavior. Changes in adolescent behavior are related to their response to the shows they watch. In this research, the main problem is whether there are.The influence of the intensity of watching the soap opera Dari Jendela SMP on changes in adolescent behavior at SMP Negeri 4 Semende Darat Laut. The soap opera Dari Jendela SMP is very popular among teenagers, especially at the junior high school level and it is assumed that many of its shows affect the behavior of teenagers, especially junior high school students. This research method uses quantitative research with field research methods (field research). This study uses a causal approach, namely researchers investigatecause effect relationship between two variables. The sample in this research amounted to 54 respondents-who were students of SMP Negeri 4 Semende Darat Laut who watched the soap opera Dari Jendela SMP. The research instrument in this study was tested using validity and reliability tests. Then the data analysis techniques used in this research are correlation analysis, simple linear regression, t test, and coefficient of determination test. The results of the study indicate that there is an influence from the soap opera Dari Jendela SMP on changes in adolescent behavior at SMP Negeri 4 Semende Darat Laut. This can be seen through the results of the t test which shows that the value of tcount ttable is 7.374 0.268. The correlation between the soap opera variable (X) and the adolescent behavior variable (Y) is quite strong, namely 0.715. The results of the coefficient-determination-test shows the influence-change-behavior of adolescents in SMP Negeri 4 Semende Darat Laut after watching the soap opera Dari Jendela SMP by 51.1% while the remaining 48.9% is outside-influence. Keywords: soap operas, adolescent behavior, SMP Negeri 4 Semede Darat Laut